See Jane entertain: Exploring a conceptual model of the effects of (semi)fictional entertainment on attitude towards female politicians. Issue 3 (3rd July 2021) - Rasul, Azmat
ABSTRACT: In political campaigns, candidates and parties frequently use biographical films based on politicians' life stories to attract voters during election years. However, little academic attention is paid to investigating the cognitive and affective influences of biographical political movies on viewers' attitudes. This study explores the psychological processes underlying these influences, which might change audiences' attitudes towards political protagonists in the movies. Specifically, this study focuses on the mediating role of narrative transportation and enjoyment as psychological influences affecting viewers' attitudes towards female politicians in the biographical films. Using data from 331 participants in an experimental study, a conceptual model was tested, which yielded significant results. The study found that enjoyment and narrative transportation experienced during exposure to biographical films positively influenced viewers' attitude towards the lead character depicted as a female politician. These findings contribute to and provide important clarification to the existing literature and have both methodological and practical implications.